"Everybody Needs Their Story to Be Heard": Motivations to Participate in Research on LGBTQ Criminal Offending. Issue 6 (3rd June 2022) - Panfil, Vanessa R.
ABSTRACT: Queer criminology must contend with many social, political, and disciplinary concerns, which include existing negative representations of LGBTQ people. Queer criminologists have noted the potential pitfalls of studying LGBTQ people's criminal offending, including perpetuating stigmatizing stereotypes, and expanding criminal justice administrative projects to LGBTQ people's detriment. This article explores a counterpoint to these concerns: gay and bisexual men's own reasons for participating in criminological research. Their reasons for discussing their gang, crime, and violence involvement illustrate their desire to help others, including telling their story so that other LGBTQ people will not follow their path and choices, and helping the researcher pursue a criminal justice degree and scholarly career. These responses suggest that responsible queer criminological research is valued among the populations we study, and they contain implicit strategies for criminological methods.